Effect of Tranexamic Acid after Cardiac Surgery in Children - Hassan, MK; Hasan, KA; Salam, ABMA; Razzak, A; Ferdous, S; Maruf, MF; Ahmed, MU; Haq, N; Ahsan, NAK (Cardiovascular Journal, 2011)
Background: The antifibrinolytic drug tranexamic acid (TA) decreases blood loss in Pediatric patients under going cardiac Surgery. However its efficacy has not been extensively studied in children. Method: We examined 750 children under going cardiac surgery form 2004 to 2007 in National Institute of Cardiovascular Diseases (NICVD), 379 children in the Tranexamic Acid group (TA) and 371 included in placebo (P) group. After induction of anesthesia and prior to skin incision, patients received either tranexamic acid (10mg/kg followed by 1mg/kg/hr) and saline placebo. After admission to intensive care unit total blood loss and transfusion requirements during the first12 hours were recorded. Result: Children who were treated with tranexamic acid had 24% less total blood loss (26±7 vs 34±17 ml/kg) compared with children who received placebo (p<0.05). Additionally, the total transfusion requirements, total donor unit exposure and financial cost of blood components were less in the tranexamic acid group. Conclusion: Tranexamic acid can reduce perioperative blood loss in children undergoing cardiac surgery. Keywords: Tranexemic acid; Cardiac surgery; Post operative; bleeding DOI: http://dx.doi.org/10.3329/cardio.v1i2.8127 Cardiovasc. j. 2009; 1(2) : 189-192